Very Delayed Remote Ischemic Post-conditioning Induces Sustained Neurological Recovery by Mechanisms Involving Enhanced Angioneurogenesis and Peripheral Immunosuppression Reversal - Doeppner, Thorsten R.; Zechmeister, Bozena; Kaltwasser, Britta; Jin, Fengyan; Zheng, Xuan; Majid, Arshad; Venkataramani, Vivek; Bähr, Mathias; Hermann, Dirk M. (Frontiers in Cellular Neuroscience, 2018)
Ischemic conditioning is defined as a transient and subcritical period of ischemia integrated in an experimental paradigm that involves a stimulus of injurious ischemia, activating endogenous tissue repair mechanisms that lead to cellular protection under pathological conditions like stroke. Whereas ischemic pre-conditioning is irrelevant for stroke treatment, ischemic post-conditioning, and especially non-invasive remote ischemic post-conditioning (rPostC) is an innovative and potential strategy for stroke treatment. Although rPostC has been shown to induce neuroprotection in stroke models before, resulting in some clinical trials on the way, fundamental questions with regard to its therapeutic time frame and its underlying mechanisms remain elusive. Hence, we herein used a model of non-invasive rPostC of hind limbs after cerebral ischemia in male C57BL6 mice, studying the optimal timing for the application of rPostC and its underlying mechanisms for up to 3 months. Mice undergoing rPostC underwent three different paradigms, starting with the first cycle of rPostC 12 h, 24 h, or 5 days after stroke induction, which is a very delayed time point of rPostC that has not been studied elsewhere. rPostC as applied within 24 h post-stroke induces reduction of infarct volume on day three. On the contrary, very delayed rPostC does not yield reduction of infarct volume on day seven when first applied on day five, albeit long-term brain injury is significantly reduced. Likewise, very delayed rPostC yields sustained neurological recovery, whereas early rPostC (i.e., <24 h) results in transient neuroprotection only. The latter is mediated via heat shock protein 70 that is a well-known signaling protein involved in the pathophysiological cellular cascade of cerebral ischemia, leading to decreased proteasomal activity and decreased post-stroke inflammation. Very delayed rPostC on day five, however, induces a pleiotropic effect, among which a stimulation of angioneurogenesis, a modulation of the ischemic extracellular milieu, and a reversal of the stroke-induced immunosuppression occur. As such, very delayed rPostC appears to be an attractive tool for future adjuvant stroke treatment that deserves further preclinical attention before large clinical trials are in order, which so far have predominantly focused on early rPostC only.